2018
DOI: 10.1016/j.jaci.2018.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Treating insect-bite hypersensitivity in horses with active vaccination against IL-5

Abstract: Our therapeutic vaccine inducing autoantibodies against self IL-5 brings biologics to horses, is the first successful immunotherapeutic approach targeting a chronic disease in horses, and might facilitate development of a similar vaccine against IL-5 in human subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
102
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(112 citation statements)
references
References 49 publications
7
102
0
3
Order By: Relevance
“…In addition, we observed increased T‐cell numbers in the bronchoalveolar lavage fluid but not in the lung tissue of bite‐sensitized mice challenged with the mosquito SGE . Many other works have shown the presence of eosinophils in the arthropod bite site of different host species . Of note, the proportion of eosinophils and neutrophils in the skin following bite may vary depending on the haematophagous arthropod studied, on the vertebrate host species and on their immune status (naïve versus immune/sensitized), a finding also observed in our study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In addition, we observed increased T‐cell numbers in the bronchoalveolar lavage fluid but not in the lung tissue of bite‐sensitized mice challenged with the mosquito SGE . Many other works have shown the presence of eosinophils in the arthropod bite site of different host species . Of note, the proportion of eosinophils and neutrophils in the skin following bite may vary depending on the haematophagous arthropod studied, on the vertebrate host species and on their immune status (naïve versus immune/sensitized), a finding also observed in our study.…”
Section: Discussionsupporting
confidence: 82%
“…37 Many other works have shown the presence of eosinophils in the arthropod bite site of different host species. [75][76][77][78][79] Of note, the proportion of eosinophils and neutrophils in the skin following bite may vary depending on the haematophagous arthropod studied, on the vertebrate host species and on their immune status (na€ ıve versus immune/sensitized), a finding also observed in our study.…”
Section: Discussionsupporting
confidence: 68%
“…To our knowledge, this approach has not been previously reported in ruminants. One recent study reported the effectiveness of IL‐5 vaccination in reducing eosinophilia and insect‐bite hypersensitivity in horses . As only small amounts of reasonably easy‐to‐prepare reagents were needed, this approach was considered more cost‐effective and feasible for large animal experimentation, such as sheep.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of the atopic cytokine milieu alone already induced a significant TSLP upregulation, and when combined with Pam3CSK4 or Poly (I:C), it synergistically further upregulated TSLP expression. In skin allergic conditions including IBH, clinical signs are exacerbated by secondary bacterial infections . As mentioned, Pam3CSK4 is a constituent of bacterial membranes recognized by TLR1/2 heterodimers .…”
Section: Discussionmentioning
confidence: 99%